COMPARATIVE ANALYSIS OF TAX INCENTIVES FOR ELECTRIC VEHICLES AND ECONOMIC IMPACT ESTIMATION IO ANALYSIS - Dharmawan Nur Muhamad; Muhammad Heru Akhmadi (Universitas Multimedia Nusantara, 2025)
The Indonesian government has set a Net Zero Emissions (NZE) target by 2060, requiring a transformation in both the energy and transportation sectors. A key strategy to achieve this goal is the acceleration of the Battery Electric Vehicle (BEV) ecosystem. To support this acceleration, the government has introduced three central tax incentive schemes: PPnBM DPP 0%, PPnBM DTP, and PPN DTP. The coexistence of these incentives raises questions regarding their effectiveness and efficiency, especially amid budgetary constraints. This study aims to compare the three incentives to identify the most optimal scheme. A mixed-method approach is applied, combining qualitative interviews with quantitative analysis using the 2024 Input-Output Table updated through the RAS method. The findings show that PPnBM DTP yields the highest economic output impact, aligning with tax authority perspectives and indicating its potential as an effective fiscal policy tool in future budget allocations.